Prosumer recruitment framework for prosumer community groups in smart-Grid - Rathnayaka, A.; Potdar, Vidyasagar; Dillon, T.; Hussain, O. (C R L Publishing Ltd., 2015)
© 2015 CRL Publishing Ltd.Smart Grid (SG) achieves bidirectional energy and information flow between the energy-user and the utility grid, allowing conventional energy-users to become prosumers, who not only generate green energy, but also return the surplus energy back to the utility-grid. Managing these energy-sharing prosumers is a pivotal requisite in SG, and making goal-oriented prosumer community groups is an effective choice to accomplish that. However, developing sustainable prosumer community groups is challenging and one of the key challenges is recruiting dynamic prosumers to the community groups. In this research paper, we address this challenge by presenting an innovative framework for prosumer recruitment in prosumer community groups. The current literature has overlooked this challenge, making our work novel within the research field. The proposed prosumer recruitment framework suggests the use of iterative evaluation process to proactively monitor the quality of service delivered by registered prosumers before assigning them to the prosumer community groups. We demonstrate the functionality of the framework using energy behaviour dataset of 500 prosumers. Furthermore, we present performance benchmarks to validate the framework's ability to identify the dynamic prosumers within the dataset, and to assign the prosumers to the appropriate prosumer community groups.